Analysis of Factors Related to The Implementation of Case Management Care at The Badung Regency Hospital, Bali - Ni Luh Putu Dina Susanti; Luh Gde Nita Sri Wahyuningsih (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Case management is a collaborative process involving the planning, coordination, monitoring, and evaluation of services provided to patients to meet their optimal health needs. This study aims to examine the factors associated with the implementation of case management care. This analytical cross-sectional study was conducted at Badung Regency Hospital, Bali. A total of 248 healthcare professionals-including doctors, nurses, and midwives who met the inclusion criteria participated in the study. Data were collected using a structured questionnaire and analysed through univariate, bivariate (Chi-square), and multivariate (binary logistic regression) methods. Chi-square analysis revealed that case manager knowledge, hospital management support, institutional policies, and multidisciplinary team collaboration were significantly associated with the implementation of case management (p < 0.05). The most influential factors were case manager knowledge (AOR = 21.16; 95% CI: 1.66-56.07) and multidisciplinary team collaboration (AOR = 13.2; 95% CI: 1.72-100.93). The findings suggest that enhancing case managers' knowledge and fostering stronger interprofessional collaboration may significantly improve the implementation of case management care in hospital settings Keywords: Case management, Case manager knowledge, Collaboration, Hospital care